(untitled) (Annals of Medical Research, 2023)
Aim: Smoking increases the risk of Graves’ orbitopathy (GO) in patients with Graves’ disease (GD). Therefore, smoking cessation should be recommended to all patients with GD. This study aimed to investigate whether smoking cessation recommendations were taken into account in patients with GD and whether there was a difference in terms of smoking cessation between those with and without GO. Materials and Methods: Smoking status of the cases followed up with GD, who were active smokers when diagnosed, were questioned by telephone visit. The relationship of these data with the presence of GO was evaluated. Results: 74 smokers with GD were included in the study. All patients were advised to quit smoking by their physicians. While the number of cigarettes was 20 (10-22)/day at the first visit, the current cigarette use was 7 (0-15)/day, (p<0.001). Forty-nine (66.2%) of the patients had GO. It was found that 49% of patients with GO and 36% of those without GO quit smoking (p=0.28). The decrease in number of cigarettes/day after physician’s recommendation was significantly higher in patients with GO than patients without GO (-95.4% vs. -54.5%), (p=0.02). Conclusion: Although the importance of smoke cessation was emphasized in all patients with GD, we observed that smoking cessation advice was more followed in the GO group in our study. Explaining in detail that smoking in GD may worsen the course of the disease and impair the quality of life in the possible development of GO, may lead patients to consider smoking cessation recommendations more.